Purchasers Perception on Packaging Formal Design: A Comparative Case Study on Luxury Goods Merchandizing - Khwanrat Chind; Nopadon Sahachaisaeree (My University, 2012)
Perception on product appearance could enhance customers' credentials for product quality and increase the potentiality of purchase. In this study a test by using a set of 3D simulated pictures as stimuli is designed to evaluate how consumers perceived product necessity of cognitive and affective perception leads to the purchasing decision by means of a structured questionnaire. Finally, the study comes up with an initial set of design guideline for packaging that convinces consumers to purchase the product.
Keywords: Purchasing decision; Guideline; Consumer Packaging Perceptions and Trends